Silicon Anode with High Initial Coulombic Efficiency by Modulated Trifunctional Binder for High‐Areal‐Capacity Lithium‐Ion Batteries. Issue 20 (8th April 2020) - Li, Zeheng; Zhang, Yaping; Liu, Tiefeng; Gao, Xuehui; Li, Siyuan; Ling, Min; Liang, Chengdu; Zheng, Junchao; Lin, Zhan
Abstract: High‐capacity electrode materials play a vital role for high‐energy‐density lithium‐ion batteries. Silicon (Si) has been regarded as a promising anode material because of its outstanding theoretical capacity, but it suffers from an inherent volume expansion problem. Binders have demonstrated improvements in the electrochemical performance of Si anodes. Achieving ultrahigh‐areal‐capacity Si anodes with rational binder strategies remains a significant challenge. Herein, a binder‐lithiated strategy is proposed for ultrahigh‐areal‐capacity Si anodes. A hard/soft modulated trifunctional network binder (N‐P‐LiPN) is constructed by the partially lithiated hard polyacrylic acid as a framework and partially lithiated soft Nafion as a buffer via the hydrogen binding effect. N‐P‐LiPN has strong adhesion and mechanical properties to accommodate huge volume change of the Si anode. In addition, lithium‐ions are transferred via the lithiated groups of N‐P‐LiPN, which significantly enhances the ionic conductivity of the Si anode. Hence, the Si@N‐P‐LiPN electrodes achieve the highest initial Coulombic efficiency of 93.18% and a stable cycling performance for 500 cycles at 0.2 C. Specially, Si@N‐P‐LiPN electrodes demonstrate an ultrahigh‐areal‐capacity of 49.59 mAh cm −2 . This work offers a new approach for inspiring the battery community to explore novel binders for next‐generation high‐energy‐density storage devices. Abstract : Herein, a binder‐lithiation strategy is proposed for ultrahigh‐areal‐capacity silicon (Si) anodes. A hard/soft modulated trifunctional network binder (N‐P‐LiPN) is constructed. The Si anode using an N‐P‐LiPN binder achieves a highest ICE of 93.18% and an ultrahigh‐areal‐capacity of 49.59 mAh cm −2 . This work offers a new approach for inspiring the battery community to explore novel binders for next‐generation high‐energy‐density storage devices.